Hegemony and Organic Intellectuals Figures in Rio Johan’s Post-Apocalyptic Novel Buanglah Hajat Pada Tempatnya - Natanael Ricky Putra; Djoko Saryono; Karkono Karkono (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2025)
This study investigates the workings of hegemony in Rio Johan’s post-apocalyptic novel Buanglah Hajat pada Tempatnya (Dispose of Waste in Its Proper Place). Guided by Antonio Gramsci’s theory of hegemony and the conventions of post-apocalyptic literature, the research asks how power is negotiated and sustained in a dystopian society. Using a descriptive qualitative approach, the study highlights the role of organic intellectuals, represented by Pak Tua (the Old Man) and Si Bocah (the Boy), in transmitting ideology to a community of survivors. The findings reveal that hegemony in this narrative emerges through everyday practices surrounding a single functional toilet and oral traditions within a waiting line. While the research contributes a new perspective by linking hegemony to post-apocalyptic settings—an underexplored area—its scope is limited to the analysis of a single text or novel.